Hubungan Antara Perilaku Ibu dan Lingkungan Fisik Rumah dengan Kejadian Tuberkulosis Paru Anak di Kota Pekalongan - Mudiyono, Mudiyono; Wahyuningsih, Nur Endah; Adi, M. Sakundarno (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2015)
Background: Children’s Tuberculosis (TB) in Indonesia at 2013 was fourth ranks in the world. The cases of children’s pulmonary tuberculosis in Pekalongan at 2013 be amounted 88 (32%) of the total cases of TB (271), greater than 8% of national cases. Children’s pulmonary tuberculosis is a disease that can be cured and are not duly claimed the lives of children. The purpose of this study is analyze the relationship between the mother's behavior and physical environment house of children with the incidence of children’s pulmonary tuberculosis in Pekalongan City.Methods: The study was observational with case control design. The cases are pulmonary tuberculosis patients and control are child is not a child’s pulmonary tuberculosis. The subjects were 50 cases and 50 controls. Results: The results of the bivariate analysis are associated with incidence population density with children’s pulmonary tuberculosis (p = <0.001), ventilation (p = 0.004), temperature of room (p = 0.036), density occupancy (p = <0.001) and natural lighting (p = 0.016). The results of multivariate analysis are risk factor for the incidence of children’s pulmonary tuberculosis with mother’s knowledge (p = 0.049; OR = 2.918; 95% CI = 1.005 to 8.472), density occupancy (p = 0.020; OR = 3.379; 95% CI = 1.212 to 9.417), humidity (p = 0.025; OR = 3.236; 95% CI = 1.156 to 9.058) and ventilation (p = 0.022; OR = 3.224; 95% CI = 1.182 to 8.797).Conclusion: The density occupancy, humidity, ventilation, mother’s knowledge are a risk factor pulmonary TB incidence of children in Pekalongan City. Keywords: Behavior Mother, the physical environment house, children’s pulmonary tuberculosis, Pekalongan City.